Disturbance intensity drives structural, compositional and diversity attributes in tropical dry forests of Central India - Satendra Kumar Rathaude; Shairq Irtiqa; P.P. Abdul Rahim; Zishan Ahmad Wani; Subashree Kothandaraman; Javid Ahmad Dar (Trees, Forests and People)
Disturbance intensity plays an important role in influencing the structural and functional dynamics of ecosystems. The present study was undertaken in the tropical dry deciduous forests of Central India under varying disturbance intensities to understand their influence on structure, diversity and compositional attributes. In total, 242 rectangular plots of 0.5 ha each (50 m × 100 m) were laid in each 8 km2 grid for phytosociological analyses and assessment of disturbance factors and levels. The plots were categorized into four types based on the level of disturbance intensity: 0–20 % {undisturbed forest (UDF)}, 21–40 % {least disturbed forest (LDF)}, 41–60 % {moderately disturbed forest (MDF)} and >60 % {highly disturbed forest (HDF)}. Among the 242 plots, 48, 56, 72 and 66 plots come under UDF, LDF, MDF and HDF categories respectively. The predominant disturbance factors in HDF were fire and fuelwood collection, whereas in the case of MDF, grazing and cut stems were dominant. A total of 202 species (120 genera, 45 families) of adult trees (≥10 diameter at breast height (DBH)) were recorded across the disturbance intensity gradient, with highest species richness in UDF (175 species) and the lowest in HDF (145 species). A significant variation in the stand structure, species composition, richness and tree diversity (Shannon (H′) and Simpson (D) index) has been found across the disturbance intensity gradients. The plots with the highest disturbance intensity (HDF) had the significantly lowest tree density (p < 0.001), basal area (p < 0.001), species richness (p < 0.001), and tree diversity: H′ (p < 0.01), D (p < 0.01) than UDF, LDF and MDF intensity gradients. The diameter-class distribution showed high percentage of small-sized (11–30 cm) trees in UDF (68 %) and LDF (60 %), whereas the medium-sized trees (31–60 cm) were high in MDF (48 %) and HDF (53 %) respectively. The current findings highlight the profound impact of varying disturbance intensities on stand structure, composition and diversity, emphasizing an urgent need for restoration, protection, conservation, and sustainable management for long-term ecosystem services.